Toothbrush with Saliva Suction Tube for Bedridden Patients - รัตนเดชสกุล, นัชนพ (Journal of Health Science of Thailand, 2022)
A family-doctor clinic in association of Mahasarakham hospital has the dentists who are responsible for taking care of 31 bedridden patients whose ages are 68.35 in average. There are 44 caregivers staying in the same place. From the 20-year national strategy of public health, a purpose is to extend the average age of Thai population not being less than 75 years. In other words, they should have an ability to take care of themselves. The oral health has a significant influence on the overall health and the length of life. One of the related factors with long lifespan is to have teeth to chew food. The bedridden patients are not capable of cleaning their own oral cavities. Thus, they need help from the caregiver to tend their oral cavities correctly. In order to maintain the oral hygiene and protect risks of disease, the patients should be cleaned their oral cavities at least once every day. The objective of this study was to develop a toothbrush with suction tube which could be used with the patients’ suction machines at homes together with the correct pose of brushing teeth. With this innovation, caregiver could clean the patients’ teeth effectively in order to decrease aspiration and reduce choke of saliva while brushing, reduce pathogen that affect to aspiration pneumonia, decrease dental caries and gingivitis in bedridden patient. The production details were described in the article. It was found that the toothbrush had functioned properly. With this innovation the processing time for tooth brushing reduced from 20.2 minutes to 12.4 minutes. Thus, this innovation could help improve dental health in bedridden patients. It should be widely promoted in other areas.